On the distance domination number of bipartite graphs - Doost Ali Mojdeh; Seyed Reza Musawi; Esmaeil Nazari (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2020)
‎A subset D ⊆ V(G) is called a k-distance dominating set of G if every vertex in V(G)-D is within distance k from some vertex of D‎. ‎The minimum cardinality among all k-distance dominating sets of G is called the k-distance domination number of G. ‎In this note we give upper bounds on the k-distance domination number of a connected bipartite graph‎, ‎and improve some results have been given like Theorems 2.1 and 2.7 in [Tian and Xu‎, ‎A note on distance domination of graphs‎, ‎Australasian Journal of Combinatorics‎, ‎43 (2009)‎, ‎181-190]‎.